ILCA's monitoring activities in Kenya: Report to the Government of Kenya - International Livestock Centre for Africa (International Livestock Centre for Africa, 1978)
Describes the monitoring Programme carried out by ILCA covering phase II of the Kenya Livestock Development Project, and the six components included. Also describes a two-tiered monitoring system consisting of intensive studies of carefully selected samples and an extensive data collection network concentrating on key indicators. Discusses initial results from the Kenya monitoring Programme.